Free space microwave interferometer technique for dielectric measurements / Munawir Mohammad - Mohammad, Munawir (1998)
In the past, a free-space techniques has been used for the measurement of dielectric constant and loss tangent using short-circuited line method and reflection and transmission coefficient method. A microwave interferometer technique is implemented on the freespace microwave measurement system consisting of transmit and receive spot focusing horn lens antenna, a network analyzer, mode transitions and a computer. The dielectric constants and loss tangents will be measured for standard materials such as Teflon and Polyvinyl-Chioride (PVC). A free-space measurement system operating in the 8 - 12,5 GHz frequency range is used to measure the reflection and transmission coefficients, Sn and S21 of the planar samples, sandwiched between composite reflectors